Avaliação física e radiográfica dos carpos, tarsos e articulações interfalangeanas de touros de raças zebuínas em regime de colheita de sêmen - Motta, Guilherme Augusto [UNESP] (2014)
Degenerative joint diseases like osteoarthritis and osteochondrosis are highly correlated to reproductive failure by bulls. This clinical and radiological study aimed the evaluation of carpal, tarsal and interphalangeal lesions in zebu bulls under a crop of semen. The three age-based experimental groups were constituted by twenty-one specimens of beef bulls, as follows; GI, up to four years old animals, GII from four to eight years-old and GIII above eight years old. The main clinical signals observed were conformational change in joints, synovial effusion, peripheric venous engorgement and long-timed decubitus upkeep. Population presented moderate clinical manifestation and radiographical score without sensitive semen alteration pattern. Elder specimens presented more severe joint lesions in comparison to younger ones. It was possible to identify in the carpi several alterations, as follows: discrete to difuse osteophytosis, subchondral cysts, cartilaginous flaps, bone fragmentation, congruence loss, osteitis, and ankylosis; tarsal lesions presented the same pattern. Interphalangeal joints presented osteophytosis, osteitis in the distal phalanx and entesiophytosis. Individual’s body weight showed high statistical correlation to both radiographical score and age. GI group had superior values of espermatic concentration and lower percentages of minor defects. Semen quality does not presented alterations even with presence of lesions as identified through instrumental and clinical exams, despite positive correlation of age and radiographical score to group age